Validation of a solid phase extraction technique for the determination of halogenated acetic acids in drinking water - Sadia Waseem,; Md. Pauzi Abdullah, (Universiti Kebangsaan Malaysia, 2010)
Haloacetic acids (HAAs) are one of the most common disinfection by-products formed during chlorination of drinking water. An analytical method involving solid phase extraction (SPE) followed by gas-chromatograph mass-spectrometry (GC-MS) was developed and optimized using experimental design to determine the HAAs in water. Selectivity, percent recovery, and detection limit studies were carried out on a Silia-SAX (Trimethyl ammonium chloride) SPE. Under optimized conditions, average recoveries for nine HAAs spiked in drinking water samples range from 69.2% to 108.2 %. The relative standard deviation (RSD) data were found to range from 2.5 % to 12.5% based upon five repeat recovery experiments and detection limit range of 0.16 to 0.009μg/l were obtained. On this basis, SPE was studied as a possible alternative to liquid-liquid extraction (LLE) for the analysis of HAAs in water. The performance of the SPE-GC-MS with actual water samples was tested.